2021
DOI: 10.1097/qai.0000000000002590
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Perceptions of Dapivirine VR Adherence and Drug Level Feedback Following an Open-Label Extension Trial

Abstract: Background: There continues to be a need for HIV prevention options that women can initiate and use autonomously. The dapivirine vaginal ring (VR) has been shown to have a favorable safety profile and reduce the risk of HIV-1 acquisition. We report on women's experiences with VR adherence during the MTN-025/HIV Open-label Prevention Extension (HOPE) study and responses to Residual Drug Level (RDL) results. Setting: Ten women at each of the 6 HOPE resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Informing young women that it is not necessary to clean the VR during menstruation may be particularly important; results from in-depth interviews among adult women in sub-Saharan Africa with low-reported VR adherence in a 12-month open-label extension of the dapivirine VR indicate that VR removal during menses was a frequent challenge to adherence. 30 Clinic staff should counsel girls to assure them that the VR is not unhygienic to use during menstruation, tampons can still be used, and it is not necessary to clean or rinse the VR.…”
Section: Discussionmentioning
confidence: 99%
“…Informing young women that it is not necessary to clean the VR during menstruation may be particularly important; results from in-depth interviews among adult women in sub-Saharan Africa with low-reported VR adherence in a 12-month open-label extension of the dapivirine VR indicate that VR removal during menses was a frequent challenge to adherence. 30 Clinic staff should counsel girls to assure them that the VR is not unhygienic to use during menstruation, tampons can still be used, and it is not necessary to clean or rinse the VR.…”
Section: Discussionmentioning
confidence: 99%
“…The AHA study methods have been reported previously. 11,16 Male partners were recruited based on permission to contact from HOPE participants, and they provided written informed consent before data collection. FGD data collected by trained male interviewers in the local language (isiZulu) were transcribed and translated in English.…”
Section: Methodsmentioning
confidence: 99%
“…While the ring is user initiated, most trial participants have stated a preference to discuss its use with male partners, to maintain trust in the relationship, to prevent social harms, and opposition linked to male partners potentially feeling the ring during sexual intercourse. 10,11 Current and previous HIV prevention research studies have reported that male partners have expressed a keen interest to be informed of their partner's study participation and product use. 12–15…”
Section: Introductionmentioning
confidence: 99%
“…Primary healthcare services, sexual and reproductive health services, and services for mother and children are important opportunities for discussing HIV risk and offering combined prevention, not only in sub-Saharan Africa, but also in other countries, for any women who may be at risk [22]. In our search, we identified 4 articles [23][24][25][26] focused solely on women, and another 3 articles included females with males [15,16,27]. HPTN 076 [23] was a Phase II study to evaluate if rilpivirine (RPV) LA was safe as a PrEP strategy.…”
Section: Interest For Injectable Long-acting Preexposure Prophylaxis ...mentioning
confidence: 99%
“…In Africa, Naidoo et al evaluated 58 women that participated in the study HIV Open-label Prevention Study (HOPE), a posttrial of the dapivirine vaginal ring [25]. The study revealed positive and negative male roles affecting the ring use, which explained some situations of nonadherence.…”
Section: The Male Role Critically Influences the Acceptability To Vag...mentioning
confidence: 99%